Students' perceptions of the vermicompost as a potential contextual learning resources - M. Muhfahroyin; Suharno Zen (Research and Development in Education (RaDEn), 2024)
Biology learning must strengthen the character of students caring for the environment concerning general and domestic waste. Domestic waste in the form of fecal sludge is a contextual environmental problem that must be managed properly. Sludge still has a fairly high concentration of nutrient content that can be utilized. The purpose of this study was to determine students' perceptions of the benefits of vermicompost as a source of contextual biology learning. As many as 239 public and private junior high school students in Metro City participated in filling out the online questionnaire. The questionnaire was developed by referring to the environmental care character criteria from the student's perspective which includes five main indicators, namely concern for the environment, responsible attitude, student knowledge about vermicompost, student motivation for contextual learning, and commitment to developing vermicompost. Data were analyzed descriptively referring to the critical success factors (CSFs). The results of the research showed that there were 5 student perceptions regarding the character of caring for the environment, namely students gave a strongly agree perception of 38.31%, a agree perception of 41.06%, a somewhat agree perception of 18.19%, a disagree perception of 2 .04, and strongly disagree at 0.40%. Students' perceptions of their environmentally caring character are influenced by many factors, namely students' knowledge and understanding of human fecal sludge and its benefits, a sense of responsibility for environmental sustainability, and students' level of education. Those who understand environmental sustainability and the benefits of fecal sludge have the perception that fecal sludge can be utilized through vermicompost and this process can be utilized as a contextual learning resource.